If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -1(p + 17) = 4p + -2 Reorder the terms: -1(17 + p) = 4p + -2 (17 * -1 + p * -1) = 4p + -2 (-17 + -1p) = 4p + -2 Reorder the terms: -17 + -1p = -2 + 4p Solving -17 + -1p = -2 + 4p Solving for variable 'p'. Move all terms containing p to the left, all other terms to the right. Add '-4p' to each side of the equation. -17 + -1p + -4p = -2 + 4p + -4p Combine like terms: -1p + -4p = -5p -17 + -5p = -2 + 4p + -4p Combine like terms: 4p + -4p = 0 -17 + -5p = -2 + 0 -17 + -5p = -2 Add '17' to each side of the equation. -17 + 17 + -5p = -2 + 17 Combine like terms: -17 + 17 = 0 0 + -5p = -2 + 17 -5p = -2 + 17 Combine like terms: -2 + 17 = 15 -5p = 15 Divide each side by '-5'. p = -3 Simplifying p = -3
| 3x-15+2=-20 | | 10-16=12x-6x-3x-3 | | p+0.77=9.3 | | 0.3+0.6(25-c)=12 | | 5x-1=6x+11 | | 2.7h+15=0.3(10-h) | | y=4x^2-x^2 | | 200=3x+2 | | 5x-4-7x=3x+6 | | 200=3x+7 | | 9(8d*5)+13=12d-2 | | -15=-6+x | | 4r-10=2r+16 | | 5(4-2y)=8(3y-2) | | -3(6a-3)+8a=-1 | | 3.1t+7=2.6 | | 3x-6=8x-26 | | 0.8(y-5)=10 | | 5(3k-2)=4(3-5k) | | -9(2-y)-(2-y)=2 | | -x-4=3x-4 | | 6(2g-4)-(3g-7)=1 | | xy^4+x^2y=5x+3y | | 14.6=k/2.5 | | 3n+53=99 | | 3x-1=6x+8 | | 3x-6+2x+3+8x-26=180 | | 3(2x-1)-3=4(-3x+2) | | 9(3-2n)+11n=2 | | 8g+5=-3(g+2) | | y/10+5=-14 | | 2(4x-3)=(6x+4) |